What is the relationship between body mass index and reaction speed in PPLOP boxing athletes in Central Java? - Syahrizal Islam; Muhamad Husein; Akabar Kusuma Abadi; Okky Putra Alwin Pratama; Jefrio Demitrimus Nubatonis; Aljawahir Agus Kristiono; Indah Sari Dewi; Muhammad Budi Wijaya; Vince Louisse D. Salacup (Universitas Tanjungpura, 2024)
Background and Study Aim. Boxing requires an optimal balance between body weight and reaction speed. Body Mass Index (BMI) is a common measure used to assess body composition. For boxers, maintaining weight within the optimal range is crucial for peak performance. Additionally, reaction speed is a key skill in boxing; the ability to quickly respond to an opponent's moves can significantly impact match outcomes. Material and Methods. This cross-sectional study utilized quantitative data analysis. Primary data included body weight, height, and reaction speed from a sample of 12 PPLOP Central Java boxing athletes. Data normality was assessed using the Shapiro-Wilk test, while the linearity test evaluated whether the relationships between variables were linear. Bivariate correlation tests were conducted. The study used Body Mass Index and Hand Touch Reaction tests with validity levels of 0.98 and 0.323, respectively, for measuring body weight, height, and reaction speed. Results. There is a relationship between body weight and reaction speed with a sig value of .003 <0.05 with a negative relationship direction. 2. there is no relationship between height and reaction speed with a sig value of (0.798>0.05) with a negative relationship direction, 3. there is a relationship between body mass index and reaction speed with a sig value of .001 <0.05 with a negative relationship direction Conclusion. Based on the results of the study it can be concluded that there is a linear relationship between body weight and reaction speed, there is no linear relationship between height and reaction speed and there is a linear relationship between body mass index and reaction speed.